Treatment of posterior inferior cerebellar artery aneurysms using flow-diverter stents: A single-center experience - Oğuz, Şükrü (Interv Neuroradiol, 2019)
INTRODUCTION: The effectiveness and reliability of flow-diverter stents, which are commonly used in aneurysms of the anterior circulation, have been demonstrated previously. However, the use of these devices is associated with higher rates of perforator and branch ischemia following the treatment of aneurysms of the posterior circulation. METHODS: This work involved a single-center; retrospective study reviewing eight patients who had aneurysms related to the posterior inferior cerebellar artery (PICA) and who were treated with flow-diverter stents from September 2013 to May 2017. RESULTS: The mean aneurysm diameter was 7.6 mm (range, 5 to 11 mm). The types of aneurysm included five aneurysms that were saccular, two that were fusiform, and one that was dissecting. All saccular aneurysms in the neck involved the PICA origin, and one dissecting aneurysm was localized in the proximal part of the PICA. Procedural success was 100% (8/8), and there were no ischemic complications. One patient with subarachnoid hemorrhage died because of rebleeding (modified Rankin Scale (mRS), 6). Other than this patient all of the patients’ mRS scores were zero at discharge and at the clinical follow-up period (mean, 2.5 years). All of the aneurysms were completely occluded according to the latest angiographic controls (mean follow-up period of 19.5 months). CONCLUSIONS: Treatment of PICA aneurysms with flow-diverter stents showed positive results with a high rate of technical success and low complication and mortality rates. The use of flow-diverter stents in the treatment of PICA aneurysms should be considered a safe and effective endovascular treatment option.